Breast cancer and pyoderma gangrenosum: a complication after conservative surgery and radiotherapy - Kuroda, Flávia; Urban, Cicero; Mendes, Erica; Raymundo, Anelise Rocha; Fornazari, Alessandra Amatuzzi Cordeiro; Durigan, Teodora Roballo (Mastology, 2020)
Pyoderma gangrenosum (PG) is a rare, ulcerative, and painful neutrophilic dermatosis of unknown cause associated with systemic diseases and/or pathergy phenomenon in 30% of cases. We report the case of a breast cancer patient submitted to oncoplastic conservative surgery followed by adjuvant radiotherapy, with long-term progression to PG. It’s rare and challeng ing nature reinforces the need for early diagnosis to increase treatment effectiveness and reduce morbidity.